Implementation Of Mindfulness to Improve Students' Interest in Learning and Emotional Well-Being - Syifa Qurrotul Aini; Sitti Hardianti; Hasrat A Aimang (Universitas Islam Negeri Palopo, 2026)
Mindfulness has increasingly attracted attention in educational research due to its potential to enhance students’ learning outcomes and psychological well-being. While previous studies have highlighted its benefits in higher education and clinical settings, fewer discussions have focused on how mindfulness contributes to improving learning interest and emotional well-being in the school context. This article aims to explore and analyze the role of mindfulness in strengthening students’ motivation to learn and maintaining their emotional balance during the learning process. The research employs a qualitative approach through a literature review of five accredited journal publications published between 2018 and 2022 that examined similar issues with different research objects. The analysis reveals that mindfulness practices positively influence students’ engagement with learning and contribute to reduced academic stress, which in turn fosters greater emotional well-being. Findings further indicate that the implementation of mindfulness not only increases students’ learning interest but also creates a healthier learning environment. The study concludes that integrating mindfulness into school practices can be an effective strategy to balance academic demands with emotional stability. These findings imply the need for educators and policymakers to consider mindfulness-based approaches as part of broader efforts to improve the quality of teaching and learning in schools.